EKSPLORASI TEKNIK SHIBORI DAN TEKNIK BOURCI DENGAN MOTIF OCEAN DEPTH PADA BUSANA PESTA MALAM - Seri Yona Ma’ruf; As As Setiawati (Universitas Pendidikan Indonesia, 2017)
The techniques of shibori is a technique that comes from Japan and is commonly called batik Japan is different ways of decorating fabrics by means of dipping tie dye as in in the language of the West or jumputan in Indonesia. The difference is in the manufacture of textile materials with ornaments how to make patterns on the fabric and close certain parts before dyed. And different on the end result of the motive that is formed. Motif formed with techniques of shibori not only produce elements of the color but the motives are not unexpected. The technique of embroidery